The genus Micrurus Wagler, 1824 (Serpentes: Elapidae) in the Northern Brazilian Atlantic Forest, with new data on rare Micrurus potyguara - Filho, Gentil Alves Pereira; Vieira, Washington Luiz Silva; Moraes, Ricardo Lourenço-De; Alves, Rômulo Romeu Nóbrega; Delfim, Fagner Ribeiro; Freitas, Marco Antônio De; Moura, Geraldo Jorge Barbosa De; França, Frederico Gustavo Rodrigues (Zootaxa, 2026)
New World coralsnakes (Leptomicrurus Schmidt, 1937, Micruroides Schmidt, 1928 and Micrurus Wagler, 1824) are distributed in North, Central and South America, being divided into two monophyletic groups regarding the number of triads. The South American triad group is represented by 22 species inhabiting diverse habitats including tropical forests such as the Amazon and the Atlantic Forest, as well as open vegetation formations like the Cerrado and the Caatinga. There are many information gaps within these species regarding their distribution. Herein, we provide the potential distribution of three species occurring in the northern Brazilian Atlantic Forest, also known as the Pernambuco Endemism Center (PEC). In addition to the potential distributions, we furnished an identification key for the species. Finally, we added new data on morphological and color variation from examining 13 new individuals of Micrurus potyguara as well as an expansion of its geographic distribution. The variation of meristic characteristics refers to the number of ventral and subcaudal scales. The new record expanded the geographic distribution to about 200 Km south of João Pessoa in Paraíba State, the type locality, to Maragogi in Alagoas State. The potential distributions show that the main area of the species is under great pressure due to fragmentation and habitat loss.